KONSEP ETIKA POLITIK DALAM PERSPEKTIF ALI SYARI’ATI - Sugiyono Sugiyono (Sekolah Tinggi Agama Islam AL Aqidah Al Hasyimiyyah Jakarta, 2019)
Islam is present in the middle of the Arab nation which is declining ethically. Islam came by carrying out the main mission of improving the ethics of the Arabs which had far deviated from human civilization. Ethics is a value that has the purpose of happiness in life. For Islamic political thinkers, politics is closely related to ethics. In the view of Ali Syari'ati explained, that politics is a government / government system that has the responsibility of maintaining the community so that it can be safe and provide welfare facilities for its citizens as an administrative task, Ali puts Islam as a basic political ethic using four approaches; namely Islamic history, the study of the contemporary world and its needs, Islamic texts, and sensitivity to the mystical elements of religion